Results in using the Freiburger monosyllabic speech test in noise without and with hearing aids - Löhler, Jürgen; Walther, Leif Erik (European archives of oto-rhino-laryngology and head & neck, 2015)
The Freiburger Speech Test (FST) has been the gold standard in speech testing by word recognition score in Germany for many years. Recently, it has been demonstrated that for an amount of 104 test-persons there is no significant deviation within the lists. The objective of this study was to determine the percentiles of the distinct measuring situations in quiet and with noise (e.g. applied in hearing aid fitting) and the average benefit using hearing aids. In this prospective study, 623 patients with SNHL and equipped with hearing aids for at least 3 months have been investigated by means of the Freiburger monosyllabic test (FBE) without and with hearing aids and in quiet or with noise (CCITT noise, 65/60 dB signal-noise ratio) in free field conditions at 65 dB to determine the ratio of intelligibility. To investigate the different diagnostic conditions a linear mixed model was applied. The dependent binary variable corresponds to the number of understood syllables. The average age of all subjects was about 72.6 years. The average rate of understanding in the FBE without hearing aids and in quiet was 38.5 %, with hearing aids and in quiet 67.7 %, without hearing aids and with noise 22.4 %, and with hearing aids and with noise 39.8 %. All results were presented with the depending confidence intervals. The extent of hearing loss and the quality of hearing aid fitting can be successfully measured using the FST in quiet and with background noise (CCITT noise). In quiet, an average hearing improving gain of 29.2 % points and with noise a gain of 17.4 % points could be estimated with a successful hearing aid fitting.
Gesehen am 26.11.2018
Published online: 17 April 2014